2015
DOI: 10.1016/j.solmat.2014.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Controlled activation of ZnTe:Cu contacted CdTe solar cells using rapid thermal processing

Abstract: Back contacts can significantly limit CdTe solar cell performance, reducing both open circuit voltage (V oc) and fill factor (FF). Copper is an essential component of effective back contacts, but its presence in the CdTe absorber creates detrimental recombination centers. Rapid thermal processing (RTP) is demonstrated as a highly effective approach for reducing back contact barriers in CdTe solar cells contacted with ZnTe:Cu buffer layers, substantially improving both FF (>73%) and V oc (>850 mV). Current dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(63 citation statements)
references
References 39 publications
5
58
0
Order By: Relevance
“…Second, it is observed that there is significant accumulation of Cu at the Au|ZnTe interface. This observation is consistent with previous analysis of quantified SIMS results [8], which suggested that up to 80% of the Cu deposited in the ZnTe:Cu layer segregates into the gold during RTP processing. This is perhaps unsurprising as these two metals are completely miscible.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Second, it is observed that there is significant accumulation of Cu at the Au|ZnTe interface. This observation is consistent with previous analysis of quantified SIMS results [8], which suggested that up to 80% of the Cu deposited in the ZnTe:Cu layer segregates into the gold during RTP processing. This is perhaps unsurprising as these two metals are completely miscible.…”
Section: Resultssupporting
confidence: 93%
“…The RTP treatment results in significant improvement in both Voc and FF [8,9]. It is postulated that the Cu migration and ZnCd interdiffusion observed in this work are responsible for these improvements.…”
Section: Resultsmentioning
confidence: 51%
See 3 more Smart Citations